2010
DOI: 10.1093/jmcb/mjq032
|View full text |Cite
|
Sign up to set email alerts
|

TIAR and TIA-1 mRNA-Binding Proteins Co-aggregate under Conditions of Rapid Oxygen Decline and Extreme Hypoxia and Suppress the HIF-1  Pathway

Abstract: T-cell intracellular antigen (TIA)-1 and TIA-1-related protein (TIAR) are mRNA-binding proteins that can aggregate within granules under specific stress conditions. In this study, we analyzed TIAR/TIA-1 aggregation under different hypoxic conditions, and studied the effects on the hypoxia-inducible factor (HIF)-1α in different cancer cell lines. Under acute and pronounced hypoxic conditions TIAR/TIA-1 co-aggregated to granules and positive co-staining with eIF3η marker suggested these to represent stress granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Selective inhibition of translation by formation of TIAR-containing granule aggregates was shown under different stress conditions such as rapid oxygen decline and hypoxia. 33 Our observation was additionally supported by findings that TIAR is translocated to the cytoplasm after eIF2a phosphorylation, where it acts as a translational suppressor. 11 As our recent work showed that BCR-ABL1 expression leads to activation of the eIF2a phosphorylation-dependent pathway, 10 this can explain why TIAR is involved in the regulation of translation in CML cells.…”
Section: Discussionsupporting
confidence: 76%
“…Selective inhibition of translation by formation of TIAR-containing granule aggregates was shown under different stress conditions such as rapid oxygen decline and hypoxia. 33 Our observation was additionally supported by findings that TIAR is translocated to the cytoplasm after eIF2a phosphorylation, where it acts as a translational suppressor. 11 As our recent work showed that BCR-ABL1 expression leads to activation of the eIF2a phosphorylation-dependent pathway, 10 this can explain why TIAR is involved in the regulation of translation in CML cells.…”
Section: Discussionsupporting
confidence: 76%
“…Although Oxyrase consumed oxygen rapidly and effectively inside and outside the cells, CoCl 2 must enter cells to be effective, which proved to be difficult and insufficient in tissues, in marked contrast to cells, and thus Oxyrase was selected for subsequent studies. 19 As shown in Figure 3B, hypoxia was uniformly and specifically detected in hypoxic cultures as early as 20 minutes of Oxyrase incubation. For in vivo study, Oxyrase was applied topically to the cortex at the injured site of the brain by dropping artificial cerebrospinal fluid comprised of Oxyrase.…”
Section: Low-level Light Suppresses Apoptosis Induced By Hypoxiamentioning
confidence: 72%
“…Stress granules contain non-translating mRNAs, translation initiation components, and many additional proteins affecting mRNA translation [52]. To explore the possible role of stress granules in the observed effect of SAHA on HIF-1α, we performed an immunofluorescence analysis of the stress granule associated proteins, TIA-1 (T-cell intracellular antigen-1) and TIAR (TIA-1 related protein) [53]. Neither SAHA (Figure S4E) nor SAHA+MG132 (data not shown) treatments induced the formation of stress granules (Figure S4E), a phenomenon that was observed in response to Tunicamycin treatment (positive control) (Figure S4E).…”
Section: Resultsmentioning
confidence: 99%